2020
DOI: 10.1519/jsc.0000000000003901
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Profile of Elite Strength Athletes

Abstract: Strength is a heritable trait with unknown polygenic nature. So far, more than 200 DNA polymorphisms associated with strength/power phenotypes have been identified majorly involving non-athletic populations. The aim of the present study was to investigate individually and in combination the association of 217 DNA polymorphisms previously identified as markers for strength/power phenotypes with elite strength athlete status. A case-control study involved 83Russian professional strength athletes (53 weightlifter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Similarly, the seminal HERITAGE Family Study reported a maximal heritability estimate of 47% (and maternal heritability of 28%) of the individual cardiorespiratory fitness responses following 20 weeks of supervised and standardised aerobic exercise training (290). More than 200 polymorphisms have been associated with strength/power phenotypes, especially concerning athletic performance (291). For example, individuals with PPARGC1A gene codes for the peroxisome proliferator-activated receptorgamma coactivator-1α (PGC-1α) Gly482Ser (rs8192678) CC genotype had lower one-repetition maximum at baseline compared to both CT genotype counterparts and T-allele carriers (292), but demonstrated that regardless of gender, baseline strength and age, 8 weeks maximal strength training intervention is effective in improving maximal strength in most healthy people.…”
Section: Inter-individual Variability and Dose-response Heterogeneity To Physical Activity And Exercisementioning
confidence: 99%
“…Similarly, the seminal HERITAGE Family Study reported a maximal heritability estimate of 47% (and maternal heritability of 28%) of the individual cardiorespiratory fitness responses following 20 weeks of supervised and standardised aerobic exercise training (290). More than 200 polymorphisms have been associated with strength/power phenotypes, especially concerning athletic performance (291). For example, individuals with PPARGC1A gene codes for the peroxisome proliferator-activated receptorgamma coactivator-1α (PGC-1α) Gly482Ser (rs8192678) CC genotype had lower one-repetition maximum at baseline compared to both CT genotype counterparts and T-allele carriers (292), but demonstrated that regardless of gender, baseline strength and age, 8 weeks maximal strength training intervention is effective in improving maximal strength in most healthy people.…”
Section: Inter-individual Variability and Dose-response Heterogeneity To Physical Activity And Exercisementioning
confidence: 99%
“…These SNPs, associated with a larger CSA of fast-twitch fibers, were also more frequent in strength and power athletes, which suggest a favourable genetic profile. Athletic phenotypes (including muscle strength and power) are polygenic in nature, which implies that multiple polymorphisms influence these athletic phenotype (Guilherme and Lancha 2020 ; Moreland et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of those 28 SNPs, the LRPPRC rs10186876, MMS22L rs9320823, and PHACTR1 rs6905419 polymorphisms were also associated with competitive weightlifting performance. Importantly, that study was the first to demonstrate the likelihood that achieving elite status in strength sports depends on a high number of SNPs [33]. Therefore, further studies are needed to replicate those findings and to confirm whether those SNPs are associated with performance in strength-oriented sports.…”
Section: Discussionmentioning
confidence: 81%
“…To date, 62 genetic markers have been associated with strength-power athlete status [3], but only some were reported in strength sports groups (weightlifting and powerlifting). These include SNPs of CNTFR, ACTN3, AGT, AR, HIF1A, PPARA, PPARG, PPARGC1A, and other genes [3,9,17,[29][30][31][32][33][34][35][36]. Recently, Grishina and colleagues confirmed the association of three SNPs (rs12055409, rs4626333, and rs2273555) with strength measures in weightlifters, which were supported by functional evidence [31,32], whereas the most comprehensive study of elite strength athletes (weightlifters and powerlifters) to date documented 28 SNPs associated with athlete status [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation